The Innovation of MOOC Based E-Marketing to Improve Entrepreneurship Administration Management for Vocational Education Students in Industrial Revolution 4.0 Era - Andika Bagus Nur Rahma Putra; Amat Mukhadis; Tuwoso; Nurul Ulfatin; Surjani Wonorahardjo; Habiddin; Made Duananda Kartika Degeng; Tee Tze Kiong (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2020)
This research has aims to: (1) develop MOOCs based e marketing; (2) testing theattractiveness of MOOCs based e-marketing; and (3) knowing the level of effectiveness of MOOCs based e-marketing. The method in this study is research and development. The resultsof this study include: (1) the results of the e-marketing expert test and website marketing design expert test have a percentage: 81.50% (ease of accessing consumers), 84.10% (presentation of goods/services sold), 79.10 % variation of website content), 86.00% (compatibility with websitegoals), 83.70% (harmony of each page of views), 83.70% (complete description of products sold),83.70% (attractiveness of e-website marketing), 85.00% (ease of order process for consumers), 81.50% (responsible admin e-marketing), 81.50% (trouble shooting website problems); (2) MOOCs based e-marketing proved effective in improving the management of student entrepreneurship administration in the vocational sector in the Industrial Revolution 4.0 era, indicated by the results of the final ability test which showed significant differences between control classes without using e-marketing based MOOCs and experimental classes using MOOCs based e-marketing; and (3) E-marketing based MOOCs needs to be further developed because it can improve the management of entrepreneurial administration in vocational students in the Industrial Revolution era 4.0.